RFID technology for continuous monitoring of physiological signals in small animals - Volk, Tobias; Gorbey, Stefan; Lemmer, Björn (IEEE transactions on biomedical engineering, 2015)
Telemetry systems enable researchers to continuously monitor physiological signals in unrestrained, freely moving small rodents. Drawbacks of common systems are limited operation time, the need to house the animals separately, and the necessity of a stable communication link. Furthermore, the costs of the typically proprietary telemetry systems reduce the acceptance. The aim of this paper is to introduce a low-cost telemetry system based on common radio frequency identification technology optimized for battery-independent operational time, good reusability, and flexibility. The presented implant is equipped with sensors to measure electrocardiogram, arterial blood pressure, and body temperature. The biological signals are transmitted as digital data streams. The device is able of monitoring several freely moving animals housed in groups with a single reader station. The modular concept of the system significantly reduces the costs to monitor multiple physiological functions and refining procedures in preclinical research.
Gesehen am 27.11.2018
Date of publication October 13, 2014